The linguocultural concept of 疫/pandemic/пaндeмия in Chinese, English, and Russian linguistic consciousness - Yanlei Ge (Philosophy, Ethics, and Humanities in Medicine)
Abstract Background As a major public health event, the pandemic has been widely discussed across various academic disciplines. In the field of humanities, most pandemic-related studies use introspective methods such as description and interpretation, indicating to some extent subjective and one-sided conclusions. In this paper, pandemic-related linguistic information and linguistic big data serve as research materials. Based on the theory of linguocultural concepts, the study employed natural language processing methods such as the analysis of word frequency and collocation co-occurrence to conduct an in-depth empirical study of 疫/pandemic/пaндeмия as a linguocultural concept in Chinese, English, and Russian linguistic consciousness from diachronic and synchronic perspectives. Methods Based on the basic linguocultural theories, this study provides a comprehensive interpretation of the etymological data on the conceptual words 疫/pandemic/пaндeмия, its lexical interpretation, and high-frequency words and co-occurring collocations related to the pandemic in Chinese, English, and Russian text corpora in Sketch Engine. The paper also analyzes reports from the mainstream media (People’s Daily Online, BBC, and TASS) to depict and explain in detail the aspects of linguocultural concepts. The historical trends of the pandemic-related concepts in the three languages were examined by observing word frequency changes through Google Book Viewer. This hybrid empirical research framework, which combines cultural concepts with linguistic big data technology, made it possible to explore the content of linguocultural concepts in a more objective, comprehensive, and profound way. Results The study revealed that: 1) In terms of etymology, the Chinese character 疫(yi, pandemic) implies a belief that pandemics were created by ghosts and gods to render people immobile. The character 疫(yi, pandemic) is also related to the concept of a fight. The English and Russian analogues (pandemic/пaндeмия) denote the same phenomenon: a disease that spreads widely among the whole population. 2) For more than 100 years since the twentieth century, pandemics have been a more significant part of Chinese consciousness than they have been in English and Russian cultures. 3) During the COVID-19 Pandemic of 2020–2023, the total number of news reports on 疫 (yi, pandemic) in Chinese was higher than the total number of news reports in English and Russian. This indicates that Chinese media tend to pay much more attention to the COVID-19 pandemic than media in the United Kingdom and Russia in all aspects. 4) China emphasizes the containment of domestic outbreaks through stringent, proactive, and comprehensive measures, including quarantine protocols, extensive testing campaigns, and evidence-based treatment strategies. On the contrary, the United Kingdom and Russia are more concerned with the global outcomes of the pandemic. Conclusions The present study objectively and comprehensively examined the similarities and differences in the perception of and response to the pandemic as a major health event in the Chinese, English, and Russian linguistic consciousness. This paper greatly contributes to the body of research in the field of humanities, broadening the scope of studies on public health events. The findings presented in this paper have relevance at both the theoretical and methodological levels. This study provides a linguistic foundation for cross-cultural public heath communication and also holds practical significance for promoting international healthcare cooperation.